The Relationship Between Previous Childbirth Experience and Self-Efficacy Among Third-Trimester Multigravida Pregnant Women in Preparing for Childbirth at Santi Rahayu Independent Midwifery Practice, Malang Regency - Nabella Sintia Deby; Asworoningrum Yulindahwati; Didien Ika Setyarini; Ita Yuliani; Retno Dumilah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Childbirth is a complex physiological and psychological experience in which previous birth experiences may influence women's confidence in preparing for subsequent deliveries. This study aimed to examine the relationship between previous childbirth experience and childbirth self-efficacy among third-trimester multigravida pregnant women at Santi Rahayu Independent Midwifery Practice, Malang Regency. This empirical study employed a quantitative correlational design with a cross-sectional approach. The study involved 31 third-trimester multigravida pregnant women with gestational ages of 28–40 weeks who were recruited using total population sampling during March–April 2022. Data were collected using the Childbirth Experience Questionnaire version 2 (CEQ-2) and the Childbirth Self-Efficacy Inventory (CBSEI), and were analyzed using Spearman's Rank correlation test. The findings showed that 71.0% of respondents reported negative childbirth experiences and 51.6% demonstrated low childbirth self-efficacy. Statistical analysis revealed a significant positive relationship between previous childbirth experience and childbirth self-efficacy (p < 0.001) with a strong correlation coefficient (ρ = 0.600). The findings indicate that women with more positive previous childbirth experiences tend to have higher confidence in preparing for childbirth. Assessing previous childbirth experiences during antenatal care may support individualized psychological interventions to strengthen maternal confidence before labor.